Theophylline-7-acetic acid: lack of absorption and therapeutic effectiveness. Issue 4 (August 1979) - Fleetham, J A; Owen, J A; May, B; Munt, P W; Nakatsu, K
Abstract : A double-blind cross-over trial was conducted to evaluate the effectiveness of oral theophylline-7-acetic acid (T7AA) in 13 asthmatic patients. Pulmonary function tests showed no difference between T7AA and placebo. No T7AA or theophylline was found in the sera of these patients or of healthy volunteers who took T7AA tablets or syrup.